CODE MIXING AND CODE-SWITCHING FOUND IN CINTA LAURA KIEHL'S SELECTED SONGS - Pasaribu, Cintana Marito; Dianti, Hilmina Rahma; Iffah, Ida Farhatul; Putri, Intan Cahyani; Sarrohmahniyati, Sarrohmahniyati; Nargis, Nargis (VARIABLE RESEARCH JOURNAL, 2025)
This research analyzes the use of code-mixing and code-switching in selected song lyrics by Cinta Laura Kiehl. The research aims to identify the types of code-mixing and code-switching that appear in five selected songs: "You Say Aq," "Can't Live," "Have Some Fun," "We Can Do It," and "Let Me Go," and to analyze how these linguistic phenomena are used. This research employs a descriptive qualitative method by analyzing song lyrics based on Hoffman's (1991), theory of code-mixing and Poplack's (1980), theory of code-switching. Data validity is ensured through source triangulation and peer debriefing. The research results show 12 data points consisting of 3 external code-switching data and 9 outer code-mixing data. No internal code-switching or inner code-mixing was found in the five songs. The phenomena of code-mixing and code-switching occur between Indonesian and English or vice versa. This research provides insights into how both linguistic phenomena are used as creative strategies in contemporary Indonesian pop music.